Ostracod‐based reconstruction of Late Quaternary lake level changes within the Tangra Yumco lake system (southern Tibetan Plateau) - M. Alivernini; L. G. Akita; M. Ahlborn; N. Börner; T. Haberzettl; T. Kasper; B. Plessen; P. Peng; A. Schwalb; J. Wang; P. Frenzel (Journal of Quaternary Science, 2018)
Tangra Yumco, a large saline lake located in the central–southern part of the Tibetan Plateau, lies in a hydrologically closed basin and is part of a cascade lake system including Tangqung Co, Tangra Yumco and Xuru Co. The extension and position of this lake system makes it valuable for reconstructing palaeoclimatic variations through the lake history and to compare both with the adjacent lake systems. We reconstructed Late Quaternary lake level changes based on data from two lacustrine sediment cores. A micropalaeontological analysis focusing on Ostracoda was carried out combined with dating ( 14 C, 210 Pb, 137 Cs), sedimentology and stable isotope data from bulk sediment. Ostracod analysis involves the quantitative documentation of associations. An ostracod‐based transfer function for specific conductivity was applied to assess and refine lake level changes and to compare the results with other lake level reconstructions from the Tibetan Plateau for evaluating inter‐regional climatic patterns. Seven ostracod species were detected, with Leucocytherella sinensis dominating the associations followed by Leucocythere ? dorsotuberosa , Limnocythere inopinata and Tonnacypris gyirongensis . Fabaeformiscandona gyirongensis , Candona candida and Candona xizangensis were found in only a few samples and at low percentages. The synthesis of ostracod‐based environmental reconstruction and chronology for samples from Tangra Yumco reveals the evolution of the lake system during the past 17 ka. A low lake level around 17 cal ka BP is followed by a recovering until the reaching of a high stand around 8–9 cal ka BP . Subsequently, between 7.7 and 2.5 cal ka BP , it remained relatively stable with a subsequent short‐living lowstand–highstand cycle at around 2 ka. Thereafter, the ostracod‐based conductivity transfer function shows an increase of conductivity corresponding to a lake level rising phase at around 0.4 ka. The recorded changes are indicators of past climatic conditions and refine the palaeoclimatic models in this area.

Reconnaissance study of an inferred Quaternary maar structure in the western part of the Bohemian Massif near Neualbenreuth, NE-Bavaria (Germany) - J. Rohrmüller; H. Kämpf; E. Geiß; J. Großmann; I. Grun; J. Mingram; J. Mrlina; B. Plessen; M. Stebich; C. Veress; A. Wendt; N. Nowaczyk (International Journal of Earth Sciences, 2018)

P alaeoenvironmental implications of evaporative gaylussite crystals from Lonar Lake, central India - A. ANOOP; S. PRASAD; B. PLESSEN; N. BASAVAIAH; B. GAYE; R. NAUMANN; P. MENZEL; S. WEISE; A. BRAUER (Journal of Quaternary Science, 2013)
We have undertaken petrographic, mineralogical, geochemical and isotopic investigations on carbonate minerals found within a 10‐m‐long core from Lonar Lake, central India, with the aim of evaluating their potential as palaeoenvironmental proxies. The core encompasses the entire Holocene and is the first well‐dated high‐resolution record from central India. While calcite and/or aragonite were found throughout the core, the mineral gaylussite was found only in two specific intervals (4630–3890 and 2040–560 cal a BP). Hydrochemical and isotope data from inflowing streams and lake waters indicate that evaporitic processes play a dominant role in the precipitation of carbonates within this lake. Isotopic (δ 18 O and δ 13 C) studies on the evaporative gaylussite crystals and residual bulk carbonates (calcite) from the long core show that evaporation is the major control on δ 18 O enrichment in both the minerals. However, in case of δ 13 C additional mechanisms, for example methanogenesis (gaylussite) and phytoplankton productivity (calcium carbonate), play an additional important role in some intervals. We also discuss the relevance of our investigation for palaeoclimate reconstruction and late Holocene monsoon variability. Copyright © 2013 John Wiley & Sons, Ltd.

Biomarker and stable carbon isotope analyses of sedimentary organic matter from Lake Tswaing: evidence for deglacial wetness and early Holocene drought from South Africa - I. Kristen; H. Wilkes; A. Vieth; K.-G. Zink; B. Plessen; J. Thorpe; T. C. Partridge; H. Oberhänsli (Journal of Paleolimnology, 2010)